Western Balkan Integration and the EU : An Agenda for Trade and Growth - Kathuria, Sanjay (Washington, DC : World Bank, 2012)
The report suggests that improving and sustaining export performance and thereby gross domestic product (GDP) growth will require sustained improvement in foreign direct investment (FDI) inflows, pointing again to the need for significant structural reform. Despite recent increases, FDI inflows in South East Europe 5 (SEE5) remain low and below potential. The onus for encouraging FDI falls on structural reforms, given the above limits on both fiscal and monetary policy. Deeper integration within Central European free trade area (CEFTA) countries will increase market size, improve service quality, and help attract FDI. Deeper integration among SEE countries such as through the completion of the implementation of CEFTA 2006, the reduction of border frictions through the establishment of a single management of Border crossing points, the regionalization of the rules of origin among CEFTA 2006 countries, and the expansion of SEE participation in pan European/Mediterranean cumulating of origin arrangements (an ongoing process) will contribute to market contestability and the development of a larger market, thereby helping to attract FDI. Deeper integration among CEFTA countries in services could also contribute to improving service quality significantly, thereby enhancing the overall productivity of the economies. This report mentions several areas, in different sectors, where there can be opportunities for regional harmonization and cooperation, including those areas where the agenda is defined by commitments to the acquis.